2016
DOI: 10.1073/pnas.1606098113
|View full text |Cite
|
Sign up to set email alerts
|

Phasic dopamine release in the medial prefrontal cortex enhances stimulus discrimination

Abstract: Phasic dopamine (DA) release is believed to guide associative learning. Most studies have focused on projections from the ventral tegmental area (VTA) to the striatum, and the action of DA in other VTA target regions remains unclear. Using optogenetic activation of VTA projections, we examined DA function in the medial prefrontal cortex (mPFC). We found that mice perceived optogenetically induced DA release in mPFC as neither rewarding nor aversive, and did not change their previously learned behavior in respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 41 publications
6
52
1
Order By: Relevance
“…Furthermore, this activity has been shown to increase in the early stage of a classical-conditioning learning task (Schoenbaum et al, 1998; Le Merre et al, 2018). Especially, the PFC participates in the association of temporally separated events in trace-conditioning task through working-memory mechanisms (Connor and Gould, 2016), maintaining a representation of the CS accross the the CS-US interval, and this timing-association is dependent on dopamine modulation in the PFC (Puig et al, 2014; Popescu et al, 2016).…”
Section: Methods: Computational Model and Simulated Behavioral Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this activity has been shown to increase in the early stage of a classical-conditioning learning task (Schoenbaum et al, 1998; Le Merre et al, 2018). Especially, the PFC participates in the association of temporally separated events in trace-conditioning task through working-memory mechanisms (Connor and Gould, 2016), maintaining a representation of the CS accross the the CS-US interval, and this timing-association is dependent on dopamine modulation in the PFC (Puig et al, 2014; Popescu et al, 2016).…”
Section: Methods: Computational Model and Simulated Behavioral Tasksmentioning
confidence: 99%
“…For the last two decades, a great amount of experimental studies depicted which brain areas send this information to the VTA. Notably, a subpopulation of pedunculopontine tegmental nucleus (PPTg) has been found to send the actual reward signal to dopamine neurons (Kobayashi and Okada, 2007; Okada et al, 2009; Keiflin and Janak, 2015), while other studies showed that the prefrontal cortex (PFC) and the nucleus accumbens (NAc) respond to the predictive cue (Keiflin and Janak, 2015; Oyama et al, 2015; Funahashi, 2006; Connor and Gould, 2016; Le Merre et al, 2018), highly depending on VTA DA feedback projections in the PFC (Puig et al, 2014; Popescu et al, 2016) and the NAc (Yagishita et al, 2014; Keiflin and Janak, 2015; Fisher et al, 2017). However, how each of these signals are integrated by VTA DA neurons during classical-conditioning remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The VTA dopaminergic system in particular has been implicated in brain-stimulation reward and food reward, psychomotor stimulation, learning and memory formation (Yokel and Wise, 1975; De Wit and Wise, 1977; Berridge, 2007; Friedman et al, 2014; Popescu et al, 2016), and it has been shown that goal-directed behavior is promoted by dopamine release from VTA DA neurons (Gallistel et al, 1985; Phillips et al, 2003; Grace et al, 2007). Studies have shown that both the synaptic connections and intrinsic excitability of DA neurons are highly plastic dependent on the experiences of the animals (Stuber et al, 2008; Mao et al, 2011; Collo et al, 2014; Friedman et al, 2014; Gore et al, 2014).…”
Section: The Ventral Tegmental Area Structure and Reward Functionmentioning
confidence: 99%
“…The proposal linking transient changes in the firing of dopamine neurons to value learning is supported mainly by correlative studies, too numerous to mention fully (see 5 for full review) . However support also comes from a growing number of causal reports, showing that artificially induced dopamine transients, with a brevity and timing similar to the physiological prediction-error correlates, are able to drive enduring changes in behavior to antecedent cues, contexts, or events [6][7][8][9][10][11][12] . These changes are assumed to reflect value learning, however almost none of these studies investigate the informational content of the learning to confirm or refute this assumption.…”
Section: Introductionmentioning
confidence: 99%
“…, top left) revealed a main effect of cue (i.e. AX-A vs. B-BX; F(1,10)=7.567, p=0.020), a main of session (F(6,60)=7.574, p=0.000), and a session × group interaction (F(6,60)=2.442, p=0.035). The source of this interaction was due to rats in the ChR2 group showing faster acquisition of both configural discriminations (i.e.…”
mentioning
confidence: 99%